Tissue-specific expression of carbohydrate sulfotransferases drives keratan sulfate biosynthesis in the notochord and otic vesicles of Xenopus embryos - Yasuoka, Yuuri (Frontiers in Cell and Developmental Biology, 2023)
Keratan sulfate (KS) is a glycosaminoglycan that is enriched in vertebrate cornea, cartilage, and brain. During embryonic development, highly sulfated KS (HSKS) is first detected in the developing notochord and then in otic vesicles; therefore, HSKS has been used as a molecular marker of the notochord. However, its biosynthetic pathways and functional roles in organogenesis are little known. Here, I surveyed developmental expression patterns of genes related to HSKS biosynthesis in Xenopus embryos. Of these genes, the KS chain-synthesizing glycosyltransferase genes, beta-1,3-N-acetylglucosaminyltransferase (b3gnt7) and beta-1,4-galactosyltransferase (b4galt4), are strongly expressed in the notochord and otic vesicles, but also in other tissues. In addition, their notochord expression is gradually restricted to the posterior end at the tailbud stage. In contrast, carbohydrate sulfotransferase (Chst) genes, chst2, chst3, and chst5.1, are expressed in both notochord and otic vesicles, whereas chst1, chst4/5-like, and chst7 are confined to otic vesicles. Because the substrate for Chst1 and Chst3 is galactose, while that for others is N-acetylglucosamine, combinatorial, tissue-specific expression patterns of Chst genes should be responsible for tissue-specific HSKS enrichment in embryos. As expected, loss of function of chst1 led to loss of HSKS in otic vesicles and reduction of their size. Loss of chst3 and chst5.1 resulted in HSKS loss in the notochord. These results reveal that Chst genes are critical for HSKS biosynthesis during organogenesis. Being hygroscopic, HSKS forms “water bags” in embryos to physically maintain organ structures. In terms of evolution, in ascidian embryos, b4galt and chst-like genes are also expressed in the notochord and regulate notochord morphogenesis. Furthermore, I found that a chst-like gene is also strongly expressed in the notochord of amphioxus embryos. These conserved expression patterns of Chst genes in the notochord of chordate embryos suggest that Chst is an ancestral component of the chordate notochord.